Analisis Literasi Halal Bagi Pelaku Usaha di Kecamatan Modung Kabupaten Bangkalan - Halwa, Marliyatul; Faraby, Muhammad Ersya (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2024)
In Islam, all aspects of life such as worship, culture, politics and economics have been regulated in the Al-Qur'an and Hadith. Including consuming food and drinks in Islam, halala is very important to pay attention to. Halal certification is the process of ensuring that products or services comply with Islamic halal standards. In Indonesia, the Food, Drug and Cosmetic Research Institute of the Indonesian Ulema Council (LPPOM MUI) is responsible for halal certification. However, there are still many MSME business actors who have not carried out halal certification for their products, bearing in mind that by October 17 2024, all products circulating in Indonesia must be halal certified. The aim of this research is to determine the understanding and knowledge of MSME business actors in Modung District, Bangkalan Regency. related to halal literacy. The research method used is qualitative with a descriptive analysis approach, which involves interviews with informants as primary and secondary data sources. The results of the discussion show that halal literacy in Modung District, Bangkalan Regency, is still very low. MSME business actors in Modung District, Bangkalan Regency have limited understanding of halal literacy. Factors such as lack of education, lack of information, and low awareness of the importance of halal certification are the causes of low halal literacy among business actors.